Code switching in oral interactions of low proficiency Malay ESL learners / Sharifah Intan Safina binti Syed Zubir - Sharifah Intan Safina, Syed Zubir (2015)
The use of code switching (CS) in the English for Second Language (ESL) classrooms has caught the attention of many scholars. Learners, especially of low English proficiency (LEP), code switch among themselves and even with the language instructors during formal classroom sessions. Due to this phenomenon, this research focuses on CS in oral interactions of low proficiency Malay ESL learners in the English classes at a local university in Malaysia and it aims to identify the reasons for CS, to describe the types of CS employed, and also to discover the communicative intents behind the use of CS. To achieve these aims, a triangulation of research methods has been adopted. Qualitative and quantitative methods are used to analyse the data which are collected through questionnaires, audio recording and interview. Some of the main findings of this research indicate that most low proficiency Malay students: 1. Code-switch due to low proficiency rather than other factors; 2. Employ intra sentential CS; 3. Uses CS for different types of communicative intents. Besides helping language practitioners in understanding CS among low proficiency students, this research could also assist teachers in the improvements of the approaches in teaching and learning in the ESL classrooms, which in turn, support the learning process for LEP students.